Regulatory mechanisms and therapeutic potential of JAB1 in neurological development and disorders - Yu Yang; Ruying Song; Yiming Gao; Hao Yu; Shuai Wang (BMC, 2023)
Abstract c-Jun activation domain binding protein-1 (JAB1) is a multifunctional regulator that plays vital roles in diverse cellular processes. It regulates AP-1 transcriptional activity and also acts as the fifth component of the COP9 signalosome complex. While JAB1 is considered an oncoprotein that triggers tumor development, recent studies have shown that it also functions in neurological development and disorders. In this review, we summarize the general features of the JAB1 gene and protein, and present recent updates on the regulation of JAB1 expression. Moreover, we also highlight the functional roles and regulatory mechanisms of JAB1 in neurodevelopmental processes such as neuronal differentiation, synaptic morphogenesis, myelination, and hair cell development and in the pathogenesis of some neurological disorders such as Alzheimer's disease, multiple sclerosis, neuropathic pain, and peripheral nerve injury. Furthermore, current challenges and prospects are discussed, including updates on drug development targeting JAB1.